High-transparency rare-earth-doped fluoride glass and method for producing the same

Through the synergistic effect of calcium fluoride, magnesium fluoride, barium fluoride, and aluminum fluoride, combined with refined processes, the optical performance and thermal stability issues of rare earth-doped fluoride glasses have been solved, achieving high transparency and uniformity and improving the overall performance of the glass.

CN120590058BActive Publication Date: 2025-11-25QINHUANGDAO MICROCRYSTALLINE TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511087519.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-11-25
Estimated Expiration
2045-08-05

AI Technical Summary

Technical Problem

Existing rare-earth-doped fluoride glasses suffer from problems such as difficulty in balancing optical properties and thermal stability, uneven distribution of dopant elements, and precipitation of crystalline phases during the preparation process, which limit their performance improvement and wide application.

Method used

A glass matrix is ​​constructed using calcium fluoride, magnesium fluoride, and barium fluoride, combined with aluminum fluoride and rare earth elements. By precisely controlling the melting temperature and process steps, the uniformity of the composition and transparency are ensured. Ammonium fluoride is used to provide the fluorine source and reduce impurities. The raw materials are refined by ball milling, and the melting process is controlled in stages to avoid crystal precipitation.

Benefits of technology

The preparation of high-transparency rare-earth-doped fluoride glass has been achieved, which improves the optical properties, mechanical strength and thermal stability of the glass, and ensures the uniform distribution of rare earth elements and the chemical purity of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a kind of high transparency rare earth doped fluoride glass and its preparation method, belongs to glass technical field.The application selects calcium fluoride, magnesium fluoride and barium fluoride to cooperatively construct glass matrix: calcium fluoride ensures high transparency and chemical stability, magnesium fluoride improves ultraviolet transmittance and mechanical strength, barium fluoride optimizes melting fluidity and rare earth doping uniformity;Add aluminum fluoride to inhibit crystallization and enhance uniformity, rare earth elements realize optical function regulation, ammonium fluoride provides fluorine source and reduces impurities;In the preparation link, after dust removal, quicklime is reacted with pure water in proportion, calcium nitrate solution is removed with hydrogen peroxide, ammonia water and carbon dioxide control the uniform growth of calcium carbonate crystal nucleus, after plate and frame pressure filtration purification, calcium fluoride is synthesized with hydrofluoric acid in proportion and low temperature drying;After ball milling and refining raw materials, the melting temperature is controlled in stages, and the overall process precisely controls impurities, reaction completeness and microstructure, and finally a high transparency functional glass is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of glass, and relates to a high-transparency rare-earth-doped fluoride glass and a preparation method thereof. BACKGROUND

[0002] In modern material science, rare-earth-doped fluoride glasses have attracted much attention due to their excellent optical properties. These materials are widely used in laser technology, optical devices, and high-performance displays. Fluoride glasses are ideal choices for optical applications due to their high transparency and low refractive index, especially in situations requiring low optical loss and high transmittance. However, there are some technical deficiencies in the preparation process of existing rare-earth-doped fluoride glasses, which limit the further improvement of their performance and the universality of their application.

[0003] Firstly, existing technologies often lack flexibility in the composition of the glass matrix, mainly focusing on the use of single fluoride. This approach may result in a suboptimal balance between the optical properties and thermal stability of the glass. For example, the use of single calcium fluoride or aluminum fluoride may lead to insufficient transparency of the glass or poor stability under high-temperature conditions. Therefore, how to optimize material performance through the combination of multiple components of fluoride remains a challenge to be solved.

[0004] Secondly, existing aluminum fluoride and rare-earth doping processes often rely on traditional high-temperature melting methods, which may result in uneven distribution of doped elements in the glass, and even the appearance of crystalline phases, thereby affecting the optical properties. This unevenness not only affects the overall performance of the material, but also brings difficulties to subsequent practical applications. SUMMARY

[0005] To solve the above problems, the present application aims to provide a high-transparency rare-earth-doped fluoride glass and a preparation method thereof. The present application selects calcium fluoride, magnesium fluoride, and barium fluoride to cooperatively construct the glass matrix: calcium fluoride ensures high transparency and chemical stability, magnesium fluoride enhances ultraviolet transmittance and mechanical strength, and barium fluoride optimizes melting fluidity and rare-earth doping uniformity; the addition of aluminum fluoride suppresses crystallization and enhances uniformity, rare-earth elements realize optical function regulation, and ammonium fluoride provides a fluorine source and reduces impurities; in the preparation process, after the quicklime is dedusted, it is reacted with pure water in a certain proportion, the calcium nitrate solution is impurity-removed with hydrogen peroxide, ammonia water and carbon dioxide are used to control the uniform growth of calcium carbonate crystal nuclei, after plate and frame pressure filtration purification, calcium fluoride is synthesized in a certain proportion with hydrofluoric acid and dried at low temperature; after the raw materials are finely ground, the melting temperature is controlled in stages (preheating to prevent bubbles, then sufficient melting to prevent crystallization, and finally high-temperature defoaming and homogenization), the overall process precisely controls impurities, reaction completeness, and microstructure, and finally a high-transparency functional glass is obtained.

[0006] To achieve this purpose, the present application adopts the following technical solutions:

[0007] In a first aspect, the present application provides a method for preparing a high-transparency rare earth doped fluoride glass, the method comprising:

[0008] The glass matrix and the aluminum fluoride, the rare earth fluoride and the ammonium fluoride are weighed, mixed and ball milled, and then placed in a crucible to be melted to obtain a primary melt, and then clarified and homogenized to obtain a glass melt, which is injected into a mold, annealed and demolded to obtain the high-transparency rare earth doped fluoride glass.

[0009] The method for preparing the high-transparency glass calcium fluoride comprises:

[0010] W1: After the quicklime is de-dusted by a bag-type dust collector, the quicklime is mixed with pure water to obtain a calcium hydroxide slurry, which is filtered and calcined to obtain calcium oxide;

[0011] W2: The calcium oxide is mixed with nitric acid to obtain a calcium nitrate solution, and the supernatant is taken after the solution is treated with hydrogen peroxide;

[0012] W3: Ammonia water and carbon dioxide are added to the supernatant to obtain a calcium carbonate dispersion, and the calcium carbonate dispersion is filtered by a plate-and-frame filter to obtain a calcium carbonate filter cake;

[0013] W4: The calcium carbonate filter cake is mixed with hydrofluoric acid to obtain a calcium fluoride dispersion, which is filtered, low-temperature dried and purified to obtain the high-transparency glass calcium fluoride;

[0014] In a preferred technical solution of the present application, in the method for preparing the high-transparency rare earth doped fluoride glass, the glass matrix comprises the high-transparency glass calcium fluoride, magnesium fluoride and barium fluoride.

[0015] In some optional embodiments, the mass ratio of the high-transparency glass calcium fluoride to the magnesium fluoride in the glass matrix is 1:(0.2-0.25), for example, can be 1:0.2, 1:0.205, 1:0.21, 1:0.215, 1:0.22, 1:0.225, 1:0.23, 1:0.235, 1:0.24, 1:0.245 or 1:0.25, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0016] In some optional embodiments, the mass ratio of the high-transparency glass calcium fluoride to the barium fluoride in the glass matrix is 1:(0.15-0.2), for example, can be 1:0.15, 1:0.155, 1:0.16, 1:0.165, 1:0.17, 1:0.175, 1:0.18, 1:0.185, 1:0.19, 1:0.195 or 1:0.2, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0017] In some alternative embodiments, the mass ratio of the glass matrix to the aluminum fluoride is 1 : (0.08-0.1), for example, it can be 1 :0.08, 1 :0.082, 1 :0.084, 1 :0.086, 1 :0.088, 1 :0.09, 1 :0.092, 1 :0.094, 1 :0.096, 1 :0.098, or 1 :0.1, but is not limited to the listed values, other unlisted values within the range are also applicable.

[0018] The fluorinated rare earth is at least one of lanthanum fluoride, yttrium fluoride, lutetium fluoride, gadolinium fluoride, and erbium fluoride.

[0019] In some alternative embodiments, the mass ratio of the glass matrix to the aluminum fluoride is 1 : (0.08-0.1), for example, it can be 1 :0.08, 1 :0.082, 1 :0.084, 1 :0.086, 1 :0.088, 1 :0.09, 1 :0.092, 1 :0.094, 1 :0.096, 1 :0.098, or 1 :0.1, but is not limited to the listed values, other unlisted values within the range are also applicable.

[0020] In some alternative embodiments, the mass ratio of the glass matrix to the aluminum fluoride is 1 : (0.08-0.1), for example, it can be 1 :0.08, 1 :0.082, 1 :0.084, 1 :0.086, 1 :0.088, 1 :0.09, 1 :0.092, 1 :0.094, 1 :0.096, 1 :0.098, or 1 :0.1, but is not limited to the listed values, other unlisted values within the range are also applicable.

[0021] In some alternative embodiments, the first melting temperature is 500-550 °C, for example, it can be 500 °C, 505 °C, 510 °C, 515 °C, 520 °C, 525 °C, 530 °C, 535 °C, 540 °C, 545 °C, or 550 °C, but is not limited to the listed values, other unlisted values within the range are also applicable.

[0022] In some alternative embodiments, the first melting time is 30-40 min, for example, it can be 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min, or 40 min, but is not limited to the listed values, other unlisted values within the range are also applicable.

[0023] In some alternative embodiments, the second temperature of melting is 1050-1100 °C, for example, it can be 1050 °C, 1055 °C, 1060 °C, 1065 °C, 1070 °C, 1075 °C, 1080 °C, 1085 °C, 1090 °C, 1095 °C, or 1100 °C, but not limited to the listed values, other values not listed in the range are also applicable.

[0024] In some alternative embodiments, the second time of melting is 1-1.5 h, for example, it can be 1 h, 1.05 h, 1.1 h, 1.15 h, 1.2 h, 1.25 h, 1.3 h, 1.35 h, 1.4 h, 1.45 h, or 1.5 h, but not limited to the listed values, other values not listed in the range are also applicable.

[0025] In some alternative embodiments, the initial melt is heated to 1100-1150 °C, for example, it can be 1100 °C, 1105 °C, 1110 °C, 1115 °C, 1120 °C, 1125 °C, 1130 °C, 1135 °C, 1140 °C, 1145 °C, or 1150 °C, but not limited to the listed values, other values not listed in the range are also applicable.

[0026] In some alternative embodiments, the initial melt is clarified and homogenized for 1-2 h, for example, it can be 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, or 2 h, but not limited to the listed values, other values not listed in the range are also applicable.

[0027] In some alternative embodiments, the annealing temperature is 450-500 °C, for example, it can be 450 °C, 455 °C, 460 °C, 465 °C, 470 °C, 475 °C, 480 °C, 485 °C, 490 °C, 495 °C, or 500 °C, but not limited to the listed values, other values not listed in the range are also applicable.

[0028] In some alternative embodiments, the annealing time is 6-8 h, for example, it can be 6 h, 6.2 h, 6.4 h, 6.6 h, 6.8 h, 7 h, 7.2 h, 7.4 h, 7.6 h, 7.8 h, or 8 h, but not limited to the listed values, other values not listed in the range are also applicable.

[0029] In the preparation method of the high-transparency glass fluorite, as a preferred technical solution of the present application, in step W1, the mass ratio of the quicklime to pure water is 1:(0.5-1), which may be, for example, 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.85, 1:0.9, 1:0.95 or 1:1, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0030] In some optional embodiments, the calcination temperature is 650-750℃, which may be, for example, 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃ or 750℃, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0031] In some optional embodiments, the calcination time is 1-2h, which may be, for example, 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2h, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0032] As a preferred technical solution of the present application, in step W2, the mass fraction of the nitric acid is 68%-70%, which may be, for example, 68%, 68.2%, 68.4%, 68.6%, 68.8%, 69%, 69.2%, 69.4%, 69.6%, 69.8% or 70%, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0033] In some optional embodiments, the mass ratio of the calcium oxide to the nitric acid is 1:(0.8-1.2), which may be, for example, 1:0.8, 1:0.84, 1:0.88, 1:0.92, 1:0.96, 1:1, 1:1.04, 1:1.08, 1:1.12, 1:1.16 or 1:1.2, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0034] In some optional embodiments, the mass ratio of the calcium nitrate solution to the hydrogen peroxide is 1:(0.001-0.005), which may be, for example, 1:0.001, 1:0.0014, 1:0.0018, 1:0.0022, 1:0.0026, 1:0.003, 1:0.0034, 1:0.0038, 1:0.0042, 1:0.0046 or 1:0.005, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0035] In some optional embodiments, the mass fraction of the hydrogen peroxide is 6-10 wt.%, for example, it can be 6 wt.%, 6.4 wt.%, 6.8 wt.%, 7.2 wt.%, 7.6 wt.%, 8 wt.%, 8.4 wt.%, 8.8 wt.%, 9.2, 9.6 wt.% or 10 wt.%, but not limited to the listed values, other values not listed in the range are also applicable.

[0036] As a preferred technical solution of the present application, in step W3, the mass ratio of the supernatant to ammonia water is 1:(1.2-1.8), for example, it can be 1:1.20, 1:1.26, 1:1.32, 1:1.38, 1:1.44, 1:1.50, 1:1.56, 1:1.62, 1:1.68, 1:1.74 or 1:1.80, but not limited to the listed values, other values not listed in the range are also applicable.

[0037] In some optional embodiments, the mass fraction of the ammonia water is 1-3 wt.%, for example, it can be 1 wt.%, 1.2 wt.%, 1.4 wt.%, 1.6 wt.%, 1.8 wt.%, 2 wt.%, 2.2 wt.%, 2.4 wt.%, 2.6 wt.%, 2.8 wt.% or 3 wt.%, but not limited to the listed values, other values not listed in the range are also applicable.

[0038] In some optional embodiments, the volume ratio of the supernatant to carbon dioxide is 1:(0.3-0.5), for example, it can be 1:0.3, 1:0.32, 1:0.34, 1:0.36, 1:0.38, 1:0.4, 1:0.42, 1:0.44, 1:0.46, 1:0.48 or 1:0.5, but not limited to the listed values, other values not listed in the range are also applicable.

[0039] As a preferred technical solution of the present application, in step W4, the mass fraction of the hydrofluoric acid is 45%-50%, for example, it can be 45.0%, 45.5%, 46.0%, 46.5%, 47.0%, 47.5%, 48.0%, 48.5%, 49.0%, 49.5% or 50.0%, but not limited to the listed values, other values not listed in the range are also applicable.

[0040] In some alternative embodiments, the mass ratio of the calcium carbonate filter cake and the hydrofluoric acid is 1 : (0.6-1), for example, it can be 1 :0.60, 1 :0.64, 1 :0.68, 1 :0.72, 1 :0.76, 1 :0.80, 1 :0.84, 1 :0.88, 1 :0.92, 1 :0.96 or 1 :1.00, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0041] In a second aspect, the present application provides a high-transparency rare earth-doped fluoride glass.

[0042] In the present application, based on the synergistic effect of the components in optical performance, mechanical properties and melting behavior, calcium fluoride, magnesium fluoride and barium fluoride are selected as the glass matrix for high-transparency glass. Calcium fluoride is the core matrix for preparing high-transparency glass. It has low refractive index, high light transmittance and excellent chemical stability, which can ensure the transparency and stability of the glass; magnesium fluoride has excellent optical properties, especially in the ultraviolet band, it has extremely high transmittance, at the same time, its doping can improve the mechanical strength of the glass, reduce the thermal expansion coefficient and improve the impact resistance; barium fluoride has a low melting point and good optical transparency, its introduction into the glass matrix can reduce the viscosity of the glass melt, adjust the melting temperature, and at the same time, provide a more suitable environment for uniform doping of rare earth ions, and improve the flowability and uniformity of the glass.

[0043] Aluminum fluoride, as a glass network modifier, can reduce the viscosity of the glass, improve the uniformity and transparency of the glass. At the same time, it can also inhibit the precipitation of crystals, so that the glass remains amorphous at high temperatures and avoids the appearance of opaque crystal phases. In the present application, the mass ratio of the glass matrix and aluminum fluoride is 1 :0.08-0.1, which ensures that the concentration of aluminum fluoride is moderate and does not excessively weaken the mechanical properties of the glass matrix.

[0044] Rare earth fluoride can expand the glass formation domain, inhibit crystallization, improve chemical-thermal stability, and can flexibly adjust the refractive index, thermal expansion coefficient and density by substituting or embedding into the glass network. For example, lanthanum fluoride can act as a network modifier, and the lanthanum ion has a large radius, which can embed into the pores of the glass skeleton, reduce the coordination unsaturation, thereby expanding the glass formation and weakening the phase separation tendency, and at the same time, appropriately increasing the refractive index; a small amount of lutetium fluoride can inhibit grain growth and increase the viscosity window, thereby improving thermal stability and reducing the thermal expansion coefficient. In the present application, the mass ratio of the glass matrix and rare earth fluoride is 1 :(0.02-0.03), which can prevent phase separation or crystal precipitation caused by excessive rare earth ions, and at the same time, ensure the uniformity of doping.

[0045] The ammonium fluoride as fluorination agent can release fluoride ions at high temperature, further supplement the fluorine content in the glass matrix, inhibit the generation of oxide impurities, and also can reduce the formation of oxide inclusions, and improve the chemical purity of the glass. The mass ratio of the glass matrix to the ammonium fluoride in the application is 1:(0.004-0.006), which can avoid excessive fluorination agent causing volatile loss or affecting the chemical stability of the glass, and also ensure the chemical stability and transparency of the glass.

[0046] In the preparation process, the components are fully mixed by ball milling, and the powder particles are refined at the same time, which can increase the contact area of the material and promote the reaction uniformity in the melting process; the first temperature stage of the melting process is mainly used for decomposing and removing volatile impurities in the material, and preheating the material to prevent the formation of bubbles in the subsequent high-temperature melting stage; the second temperature stage is the initial melting stage of the glass matrix, which can ensure that all components are fully reacted to form a uniform initial melt, while avoiding crystal precipitation and phase separation; the high-temperature refining stage can eliminate bubbles and inclusions by improving the fluidity of the melt, and achieve full homogenization of the components, and finally obtain a high-transparency glass melt.

[0047] In the preparation process of the high-transparency glass calcium fluoride in the application, the particulate impurities possibly contained in the quicklime are removed by a bag-type dust collector, reducing the introduction of inorganic particulate impurities and avoiding the secondary pollution possibly introduced in the traditional fine screening separation. The mass ratio of the quicklime to pure water is optimized to 1:(0.5-1), ensuring complete reaction without excessive unreacted calcium oxide or causing too high slurry concentration to affect filtration and subsequent calcination.

[0048] The obtained calcium oxide is mixed with nitric acid to form a calcium nitrate solution, and a small amount of hydrogen peroxide is added to the solution. The strong oxidizing property of the hydrogen peroxide oxidizes the reducing impurities in the solution, converting them into compounds that are easy to precipitate or filter. By controlling the amount of hydrogen peroxide added, the impurities can be accurately removed without introducing secondary by-products.

[0049] Mixing the supernatant with ammonia and carbon dioxide realizes uniform generation of calcium carbonate crystal nuclei, avoids particle agglomeration, and ensures high transparency and uniformity of the final calcium fluoride particles; plate and frame filter pressing can remove impurities and residual ions in the calcium carbonate dispersion at a relatively low pressure, improving the purity of the final product while avoiding particle breakage.

[0050] In the application, the calcium carbonate is mixed with hydrofluoric acid in a mass ratio of 1:(0.6-1) to ensure complete reaction without forming by-products, ensuring the purity of the calcium fluoride particles while avoiding the volatile loss of excess hydrofluoric acid; by mixing calcium carbonate with hydrofluoric acid to prepare a calcium fluoride dispersion, and then filtering and drying at low temperature, the crystal deformation or agglomeration caused by high temperature is avoided, ensuring uniform dispersion of the calcium fluoride particles and maintaining their high transparency.

[0051] Compared with the prior art, the application has the following beneficial effects:

[0052] Based on the synergistic effect of calcium fluoride, magnesium fluoride and barium fluoride in optical performance, mechanical performance and melting behavior, the application selects them as a high transparent glass matrix: calcium fluoride as the core matrix provides low refractive index, high transmittance and chemical stability, ensuring the transparency and stability of the glass; magnesium fluoride enhances the ultraviolet transmittance, improves the mechanical strength and reduces the thermal expansion coefficient; barium fluoride improves the flowability by reducing the melt viscosity and adjusting the melting temperature, and optimizes the uniformity of rare earth ion doping;

[0053] In the application, aluminum fluoride is used as a glass network modifier to effectively reduce the glass viscosity, improve the uniformity and transparency, and inhibit the crystal precipitation to maintain the high temperature amorphous state; the rare earth element plays a regulatory function by doping to ensure the uniform distribution of ions and avoid phase separation; ammonium fluoride releases fluoride ions at high temperature to reduce the oxide impurities and improve the chemical purity, taking into account the stability and transparency; the three components synergistically optimize the optical performance, structural stability and preparation process of the glass;

[0054] The application ensures the preparation of high transparent glass by optimizing the process: in the raw material processing stage, the quicklime is reacted with pure water after impurity removal by bag type dust removal to realize complete conversion and avoid over-concentration of the slurry; in the calcium nitrate synthesis, trace hydrogen peroxide is used for precise oxidation to remove reducing impurities; in the calcium carbonate precipitation stage, ammonia water and carbon dioxide are used to cooperatively control the uniform generation of crystal nucleus, and the impurities are efficiently removed by plate and frame filter pressing; after the reaction of calcium carbonate and hydrofluoric acid, the calcium fluoride is prepared by low temperature drying, taking into account the reaction completeness, particle dispersibility and transparency; in the preparation process, the ball milling is used to refine the materials to promote the melting uniformity, the temperature is controlled in stages (impurity removal to prevent bubbles in the initial stage, sufficient reaction to inhibit crystal precipitation in the middle stage, and defoaming and homogenization at high temperature), and finally the high transparent glass melt is obtained; the impurity introduction, reaction completeness and microstructure are cooperatively controlled to ensure the optical performance of the product. DETAILED DESCRIPTION

[0055] The technical solutions of the application will be described in detail below with specific examples. The examples described herein are specific embodiments of the application, which are used to illustrate the concept of the application; all the descriptions are explanatory and exemplary, and should not be understood as limiting the embodiments of the application and the protection scope of the application. In addition to the examples described herein, those skilled in the art can also employ other technical solutions that are obvious based on the content disclosed in the claims and the description of the application, which include technical solutions that make any obvious substitutions and modifications to the examples described herein.

[0056] The chemical reagents used in the examples and comparative examples of the application are all commercially available goods without further purification or treatment.

[0057] Embodiment 1

[0058] The embodiment provides a high-transparency rare earth doped fluoride glass and a preparation method thereof, and the preparation method of the high-transparency rare earth doped fluoride glass specifically comprises the following steps:

[0059] The calcium fluoride, magnesium fluoride and barium fluoride for the high-transparency glass of a glass matrix and the aluminum fluoride, rare earth fluoride and ammonium fluoride are weighed, mixed and ball milled, and then placed in a crucible to be melted to obtain a first melt, wherein the mass ratio of the calcium fluoride to the magnesium fluoride for the high-transparency glass of the glass matrix is 1:0.24, the mass ratio of the calcium fluoride to the barium fluoride for the high-transparency glass of the glass matrix is 1:0.18, the mass ratio of the glass matrix to the aluminum fluoride is 1:0.09, the mass ratio of the glass matrix to the rare earth fluoride is 1:0.025, and the mass ratio of the glass matrix to the ammonium fluoride is 1:0.005; the first temperature for melting is 500 DEG C, the time is 35 min, the second temperature is 1055 DEG C, the time is 1 h, the first melt is clarified and homogenized at 1150 DEG C for 1.6 h to obtain a glass melt, the glass melt is injected into a mold, annealed at 480 DEG C for 7 h, demolded to obtain the high-transparency rare earth doped fluoride glass.

[0060] The preparation method of the calcium fluoride for the high-transparency glass comprises the following steps:

[0061] W1: After the quicklime is removed dust through a bag-type dust collector, the quicklime is mixed with pure water at a mass ratio of 1:0.8 to obtain a calcium hydroxide slurry; the calcium hydroxide slurry is filtered and calcined at 700 DEG C for 2 h to obtain calcium oxide;

[0062] W2: The calcium oxide is mixed with nitric acid with a mass fraction of 69% at a mass ratio of 1:1 to obtain a calcium nitrate solution, the calcium nitrate solution is treated with hydrogen peroxide with a mass fraction of 8 wt.% to obtain supernatant, wherein the mass ratio of the calcium nitrate solution to the hydrogen peroxide is 1:0.004;

[0063] W3: The supernatant is added with ammonia water with a mass fraction of 2 wt.% and carbon dioxide to obtain a calcium carbonate dispersion, wherein the mass ratio of the supernatant to the ammonia water is 1:1.5, and the volume ratio of the supernatant to the carbon dioxide is 1:0.4; the calcium carbonate dispersion is filtered through a plate-and-frame filter to obtain a calcium carbonate filter cake;

[0064] W4: The calcium carbonate filter cake is mixed with hydrofluoric acid with a mass fraction of 48% at a mass ratio of 1:0.8 to obtain a calcium fluoride dispersion, and the calcium fluoride dispersion is filtered, low-temperature dried and purified to obtain the calcium fluoride for the high-transparency glass.

[0065] Embodiment 2

[0066] The embodiment provides a high-transparency rare earth doped fluoride glass and a preparation method thereof, and the preparation method of the high-transparency rare earth doped fluoride glass specifically comprises the following steps:

[0067] The high-transparency glass fluorides of calcium, magnesium and barium and the fluorides of aluminum, rare earth and ammonium are weighed, mixed and ball-milled, and then placed in a crucible to obtain a primary melt. The mass ratio of the high-transparency glass fluoride of calcium to the high-transparency glass fluoride of magnesium is 1:0.22, the mass ratio of the high-transparency glass fluoride of calcium to the high-transparency glass fluoride of barium is 1:0.17, the mass ratio of the glass matrix to the fluoride of aluminum is 1:0.096, the mass ratio of the glass matrix to the fluoride of rare earth is 1:0.028, and the mass ratio of the glass matrix to the fluoride of ammonium is 1:0.0057. The first temperature for melting is 550°C, the time is 37 min, the second temperature is 1058°C, the time is 1.2 h, the primary melt is clarified and homogenized at 1100°C for 1.4 h to obtain a glass melt, which is injected into a mold, annealed at 470°C for 6 h, and demolded to obtain a high-transparency rare earth-doped fluoride glass.

[0068] The preparation method of the high-transparency glass fluoride of calcium is as follows:

[0069] W1: After the quicklime is de-dusted by a bag-type dust collector, the quicklime is mixed with pure water at a mass ratio of 1:0.5 to obtain a calcium hydroxide slurry. The calcium hydroxide slurry is filtered and calcined at 750°C for 1.5 h to obtain calcium oxide.

[0070] W2: The calcium oxide is mixed with nitric acid with a mass fraction of 68.7% at a mass ratio of 1:1.1 to obtain a calcium nitrate solution. After the calcium nitrate solution is treated with hydrogen peroxide with a mass fraction of 9wt.%, the supernatant is obtained. The mass ratio of the calcium nitrate solution to the hydrogen peroxide is 1:0.003.

[0071] W3: Ammonia water with a mass fraction of 1wt.% and carbon dioxide are added to the supernatant to obtain a calcium carbonate dispersion. The mass ratio of the supernatant to the ammonia water is 1:1.6, and the volume ratio of the supernatant to the carbon dioxide is 1:0.3. The calcium carbonate dispersion is filtered by a plate-and-frame filter to obtain a calcium carbonate filter cake.

[0072] W4: The calcium carbonate filter cake is mixed with hydrofluoric acid with a mass fraction of 47% at a mass ratio of 1:0.6 to obtain a calcium fluoride dispersion. The calcium fluoride dispersion is filtered, low-temperature dried and purified to obtain the high-transparency glass fluoride of calcium.

[0073] Example 3

[0074] The present embodiment provides a high-transparency rare earth-doped fluoride glass and a preparation method thereof. The preparation method of the high-transparency rare earth-doped fluoride glass specifically includes the following steps:

[0075] The fluorides of calcium, magnesium and barium and fluorides of aluminum, rare earth and ammonium are mixed and ball milled to obtain a first melt, wherein the mass ratio of the fluorides of calcium to magnesium for high transparency glass is 1:0.2, the mass ratio of the fluorides of calcium to barium for high transparency glass is 1:0.15, the mass ratio of the glass matrix to the fluoride of aluminum is 1:0.08, the mass ratio of the glass matrix to the fluoride of rare earth is 1:0.02, and the mass ratio of the glass matrix to the fluoride of ammonium is 1:0.004; the first temperature for melting is 520 DEG C, the time is 30 min, the second temperature is 1050 DEG C, the time is 1.3 h, the first melt is clarified and homogenized at 1120 DEG C for 1 h to obtain a glass melt, which is poured into a mold, annealed at 450 DEG C for 8 h, and demolded to obtain a high transparency rare earth doped fluoride glass;

[0076] The preparation method of the fluorides of calcium for high transparency glass is as follows:

[0077] W1: After the quicklime is de-dusted by a bag-type dust collector, the quicklime is mixed with pure water at a mass ratio of 1:1 to obtain a calcium hydroxide slurry; the calcium hydroxide slurry is filtered and calcined at 720 DEG C for 1 h to obtain calcium oxide;

[0078] W2: The calcium oxide is mixed with nitric acid with a mass fraction of 68% at a mass ratio of 1:0.8 to obtain a calcium nitrate solution, and the calcium nitrate solution is treated with hydrogen peroxide with a mass fraction of 6 wt.% to obtain a supernatant, wherein the mass ratio of the calcium nitrate solution to the hydrogen peroxide is 1:0.001;

[0079] W3: Ammonia water with a mass fraction of 3 wt.% and carbon dioxide are added to the supernatant to obtain a calcium carbonate dispersion, wherein the mass ratio of the supernatant to the ammonia water is 1:1.2, and the volume ratio of the supernatant to the carbon dioxide is 1:0.5; the calcium carbonate dispersion is filtered by a plate and frame filter to obtain a calcium carbonate filter cake;

[0080] W4: The calcium carbonate filter cake is mixed with hydrofluoric acid with a mass fraction of 45% at a mass ratio of 1:0.7 to obtain a calcium fluoride dispersion, which is filtered, dried at low temperature and purified to obtain the fluorides of calcium for high transparency glass.

[0081] Example 4

[0082] The embodiment provides a high transparency rare earth doped fluoride glass and a preparation method thereof, and the preparation method of the high transparency rare earth doped fluoride glass specifically comprises the following steps:

[0083] The glass matrix high-transparency glass fluorides of calcium, magnesium and barium fluoride and fluorides of aluminum, rare earth, ammonium are mixed by ball milling and then placed in a crucible to melt to obtain a first melt, wherein the mass ratio of the fluorides of calcium and magnesium for high-transparency glass in the glass matrix is 1:0.25, the mass ratio of the fluorides of calcium and barium for high-transparency glass in the glass matrix is 1:0.2; the mass ratio of the glass matrix and the fluoride of aluminum is 1:0.1, the mass ratio of the glass matrix and the fluoride of rare earth is 1:0.03, and the mass ratio of the glass matrix and the fluoride of ammonium is 1:0.006; the first temperature for melting is 530℃, the time is 40min, the second temperature is 1100℃, the time is 1.5h, the first melt is heated to 1130℃, and then clarified and homogenized for 2h to obtain a glass melt, which is injected into a mold, annealed at 500℃ for 7.5h, and demolded to obtain a high-transparency rare earth doped fluoride glass;

[0084] The preparation method of the fluoride of calcium for high-transparency glass is as follows:

[0085] W1: After the quicklime is de-dusted by a bag-type dust collector, the quicklime is mixed with pure water at a mass ratio of 1:0.7 to obtain a calcium hydroxide slurry; the calcium hydroxide slurry is filtered and calcined at 650℃ for 1.7h to obtain calcium oxide;

[0086] W2: The calcium oxide is mixed with nitric acid with a mass fraction of 70% at a mass ratio of 1:1.2 to obtain a calcium nitrate solution, and then the supernatant is obtained after the calcium nitrate solution is treated with hydrogen peroxide with a mass fraction of 10wt.%; wherein the mass ratio of the calcium nitrate solution and the hydrogen peroxide is 1:0.005;

[0087] W3: Ammonia water with a mass fraction of 1.5wt.% and carbon dioxide are added to the supernatant to obtain a calcium carbonate dispersion, wherein the mass ratio of the supernatant and the ammonia water is 1:1.8; the volume ratio of the supernatant and the carbon dioxide is 1:0.46; and the calcium carbonate filter cake is obtained by plate and frame pressure filtration;

[0088] W4: The calcium carbonate filter cake is mixed with hydrofluoric acid with a mass fraction of 50% at a mass ratio of 1:1 to obtain a fluoride of calcium dispersion, and then the fluoride of calcium for high-transparency glass is obtained by filtration, low-temperature drying and purification.

[0089] Comparative Example 1

[0090] The comparative example provides a high-transparency rare earth doped fluoride glass, which is different from the example 1 in that no magnesium fluoride is added in the preparation process of the high-transparency rare earth doped fluoride glass, and other operation steps and process parameters are completely the same as those of the example 1.

[0091] Comparative Example 2

[0092] The comparative example provides a high-transparency rare earth-doped fluoride glass, which is different from example 1 in that no rare earth fluoride is added in the preparation process of the high-transparency rare earth-doped fluoride glass, and other operation steps and process parameters are completely same as those of example 1.

[0093] Comparative example 3

[0094] The comparative example provides a high-transparency rare earth-doped fluoride glass, which is different from example 1 in that no hydrogen peroxide is added in W2, and other operation steps and process parameters are completely same as those of example 1.

[0095] The high-transparency rare earth-doped fluoride glasses of example 1 to example 4 and comparative example 1 to comparative example 3 are tested for performance, and the specific process is as follows:

[0096] The refractive index of the sample is tested according to GB / T 7962.1-2010;

[0097] The thermal expansion coefficient of the sample is tested according to GB / T 16920-2015;

[0098] Microhardness: the glass sample is cut into a glass sheet with a thickness of 2.5 mm, washed with clean water, dried, and smoothed by grinding and polishing, and the microhardness of the glass is tested by using a HVS-1000 digital microhardness tester;

[0099] The test results are shown in table 1.

[0100] Table 1: performance test results of high-transparency rare earth-doped fluoride glasses of example 1 to example 4 and comparative example 1 to comparative example 3

[0101]

[0102] From the test results of example 1 and comparative example 1, it can be seen that magnesium fluoride is a low-refractive material, and its introduction can reduce the refractive index of the overall glass. After the lack of magnesium fluoride, the proportion of other high-refractive components in the glass system increases relatively, resulting in the increase of the overall refractive index, and due to the lack of the thermal expansion adjustment effect of magnesium fluoride, the thermal expansion coefficient of the system increases; the role of magnesium fluoride in enhancing hardness is missing, resulting in a decrease in microhardness.

[0103] From the test results of example 1 and comparative example 2, it can be seen that the introduction of fluorinated rare earth can improve the refractive index and optical performance of the glass. After the lack of fluorinated rare earth component, the proportion of high-refractive components in the glass decreases, resulting in a decrease in the refractive index of the glass; the enhancement effect of the fluorinated rare earth component on hardness is weakened, so the microhardness is slightly reduced; the influence on the thermal expansion coefficient is small.

[0104] From the test results of Example 1 and Comparative Example 3, it can be seen that in the calcium nitrate solution treatment, hydrogen peroxide is used as an oxidizing agent to remove impurity ions and improve the purity of the final calcium fluoride; omission of the addition of hydrogen peroxide will result in the presence of impurity ions, thereby causing the refractive index to increase; the presence of impurity ions can interfere with the structural uniformity of the glass, resulting in a significant decrease in hardness; the effect of impurities on the coefficient of thermal expansion is relatively small.

[0105] The above description is merely a specific implementation of the present application, but the protection scope of the present application is not limited thereto. It should be understood by those skilled in the art that any changes or replacements within the technical scope disclosed by the present application can be easily conceived by those skilled in the art, and all such changes and replacements fall within the protection scope and disclosure scope of the present application.

Claims

1. A method for preparing a high-transparency rare-earth-doped fluoride glass, characterized in that, The preparation method includes: Weigh out the glass matrix and mix it with aluminum fluoride, rare earth fluoride and ammonium fluoride, ball mill it and place it in a crucible to melt it to obtain a primary melt. Clarify and homogenize it to obtain a glass melt, pour it into a mold, anneal it and demold it to obtain a high-transparency rare earth doped fluoride glass. The glass matrix includes calcium fluoride, magnesium fluoride and barium fluoride for high-transparency glass. The method for preparing the calcium fluoride for high-transparency glass is as follows: W1: Quicklime is removed from the dust using a bag filter and then mixed with pure water to react and obtain calcium hydroxide slurry; this slurry is then filtered and calcined to obtain calcium oxide. W2: Calcium oxide is mixed with nitric acid to obtain a calcium nitrate solution, which is then treated with hydrogen peroxide and the supernatant is collected. W3: Add ammonia and carbon dioxide to the supernatant to obtain a calcium carbonate dispersion; then filter the dispersion using a plate and frame filter press to obtain a calcium carbonate filter cake. W4: Calcium carbonate filter cake is mixed with hydrofluoric acid to obtain calcium fluoride dispersion, which is then filtered and dried to obtain high-transparency calcium fluoride for glass. The mass ratio of the glass matrix to aluminum fluoride is 1:(0.08-0.1); The mass ratio of the glass matrix to rare earth fluoride is 1:(0.02-0.03); The mass ratio of the glass matrix to ammonium fluoride is 1:(0.004-0.006).

2. The method for preparing a high-transparency rare-earth-doped fluoride glass according to claim 1, characterized in that: The mass ratio of calcium fluoride to magnesium fluoride in the high-transparency glass matrix is ​​1:(0.2-0.25). The mass ratio of calcium fluoride to barium fluoride in the high-transparency glass matrix is ​​1:(0.15-0.2).

3. The method for preparing a high-transparency rare-earth-doped fluoride glass according to claim 1, characterized in that: The rare earth fluorides are at least one of lanthanum fluoride, yttrium fluoride, lutetium fluoride, gadolinium fluoride, and erbium fluoride.

4. The method for preparing a high-transparency rare-earth-doped fluoride glass according to claim 1, characterized in that, In W1: the mass ratio of quicklime to pure water is 1:(0.5-1).

5. The method for preparing a high-transparency rare-earth-doped fluoride glass according to claim 1, characterized in that, In W2: The mass fraction of the nitric acid is 68%-70%; The mass ratio of calcium oxide to nitric acid is 1:(0.8-1.2); The mass ratio of the calcium nitrate solution to hydrogen peroxide is 1:(0.001-0.005).

6. The method for preparing a high-transparency rare-earth-doped fluoride glass according to claim 1, characterized in that, In W3: The mass ratio of the supernatant to ammonia water is 1:(1.2-1.8); The volume ratio of the supernatant to carbon dioxide is 1:(0.3-0.5).

7. The method for preparing a high-transparency rare-earth-doped fluoride glass according to claim 1, characterized in that, In W4: The hydrofluoric acid has a mass fraction of 45%-50%; The mass ratio of the calcium carbonate filter cake to hydrofluoric acid is 1:(0.6-1).

8. A high-transparency rare-earth-doped fluoride glass prepared by the preparation method according to any one of claims 1-7.

Citation Information

Patent Citations

  • Fluoroaluminate laser glass and preparation method thereof

    CN1541965A